Prediksi Arus Kas Bebas, Kebijakan Utang, Dan Profitabilitas Terhadap Kemungkinan Dibayarkannya Dividen Studi Empirik Pada Emiten Pembentuk Indeks Kompas 100 Di Bursa Efek Indonesia - Bram Hadianto, Herlina (Universitas Prasetiya Mulya, 2010)
The aim of this research is to know the prediction of some explanatory factors that impact on probability of public company to divide earnings to investor and fnd the accuracy rate to classify public company become two group based on some explanatory factor. First group is dividend payers company, and second group is non-dividend payers company. Some explanatory factors that we used are free cash fow, debt policy, and proftability. We employ logistic regression model as data analysis method. Our sample is taken from the Kompas 100 Index constituent public company in 2007. The results point out both debt policy and proftability are positively relationship with dividend policy and free cash fow has no signifcant relationship with dividend policy. In addition, the accuracy of all factors that used to classify both dividend payers company group and dividend non-payers company group are 69%.